The role of social media messages and content creators in shaping COVID-19 vaccination intentions - Jia, Xiaofeng; Ahn, Soyeon; Morgan, Susan E. (Frontiers in Digital Health, 2025)
IntroductionSocial media plays a crucial role in shaping health behaviors by influencing users' perceptions and engagement with health-related content. Understanding these dynamics is important as new social media technologies and changing health behaviors shape how people engage with health messages.AimThe current study explored the relationship between the characteristics of content creators, the messaging strategies employed in social media, and users' engagement with social media content, and whether these features are linked to users' behavioral intentions.MethodsThis study adopts a cross-sectional survey design. A total of 1,141 participants were recruited. We have developed a structural equation model to investigate the relationships between the characteristics of content creators, the messaging strategies employed in social media, users’ perceived HBM constructs, user engagement, and users' behavioral intentions.ResultsResults revealed that social media posts focusing on self-efficacy were linked to increased willingness to engage in healthy behaviors. Additionally, individuals who demonstrate stronger perceptions of HBM constructs—such as higher perceived susceptibility and benefits of vaccination—are more likely to engage with posts, which was associated with higher vaccination intention. Posts authored by celebrities garnered a relatively higher number of favorites, while a greater proportion of politicians as content creators was linked to increased user comment intention.ConclusionOur study underscores the potential of integrating the Health Belief Model into social media to help promote health behaviors like the COVID-19 vaccination. Furthermore, our findings offer valuable insights for professionals and policymakers, guiding them in crafting effective message strategies and selecting appropriate sources to promote health behaviors on social media platforms.